(untitled) (Proceedings of International Educators Conference, 2023)
Teaching English as a Second Language (TESL) or Teaching English to Speakers of Other Languages (TESOL) are terms for teaching English to students whose first language is not English. The terms TESL, TEFL, and TESOL differ depending on the location of the classroom and the number of students. [1] TEFL are English language programs available in countries where English is not the primary language. TEFL programs can be taught at a language school or individually with a teacher. For some jobs, the minimum TEFL requirement is a 100-hour course; however, the 120-hour course is strongly recommended, as it often leads to higher-paying teaching positions.